Organization of Independent Work of Students in The Study of Oxygen-Containing Organic Compounds - Yusufova Sabina Georgievna (Periodica Journal, 2023)
The need to form new concepts about the functional group, hydrogen bond, etc., on the one hand, and on the other hand, the expansion and deepening of existing knowledge about the structure and properties of hydrocarbons, make it possible to fully realize the cognitive abilities of students. This is facilitated by the widespread use of such forms of education as lectures followed by discussion of the material at the seminar; offsets; organization of independent work of students with a textbook when performing experimental tasks; systematic testing of knowledge. This article considers all those positions on the example of the study of individual classes of oxygen-containing compounds.
Keywords: Cognitive activity; seminar; chemical properties